2008
DOI: 10.1111/j.1365-2923.2007.02977.x
|View full text |Cite
|
Sign up to set email alerts
|

Can a district hospital assess its doctors for re-licensure?

Abstract: This study shows that the commissioning of professional services makes the implementation of an assessment process linked to appraisal feasible. However, trust-based assessment requires significant development: developmental appraisal needs protection; new instruments are needed for non-clinical specialties; PR requires specific administrative support, and guidance is required over concern thresholds and demographic effects. Disaggregated assessment data may help identify doctors with potential performance pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 3 publications
1
24
1
Order By: Relevance
“…Unlike others8 we did not find that the gender of the doctor influenced the results, although the gender of the rater did have an effect. Potential effects of ethnicity have been previously described by others noting that UK trained doctors score higher than international medical graduates,8 13 although whether this is due to true differences in knowledge and ability, cultural effects or rater preconceptions is not known. Studies on race effects on performance in non-medical settings have suggested that assessors rate higher those similar to themselves 14 15.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike others8 we did not find that the gender of the doctor influenced the results, although the gender of the rater did have an effect. Potential effects of ethnicity have been previously described by others noting that UK trained doctors score higher than international medical graduates,8 13 although whether this is due to true differences in knowledge and ability, cultural effects or rater preconceptions is not known. Studies on race effects on performance in non-medical settings have suggested that assessors rate higher those similar to themselves 14 15.…”
Section: Discussioncontrasting
confidence: 99%
“…The average ratings are high, challenging whether this process is sufficiently discriminatory to be useful. Crossley et al ,8 using the unmodified instrument across an unselected population, did observe a wider range of scores suggesting that if this tool was used on all doctors, a wider spread of ratings would be seen allowing outliers to be revealed. Feedback from patients is only one of the pieces of information that feeds into the revalidation process and needs to be triangulated with other evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 several multisource feedback tools are used to assess teamwork and communication, such as the sheffield Peer review assessment tool (sPrat) and mini Peer assessment tool, which have been validated by various groups. 48,49 Designed in accordance with GmP guidelines, the sPrat is used in a number of settings to assess workplacebased performance. although the feasi bility and validity of multisource feedback and patient rating instruments has been reported in various studies, these tools have only been tested on careergrade practi tioners and not specialists; 26,49 no multisource feedback tool has yet been approved for use in specialist recertifica tion.…”
Section: Outcome-based Assessmentmentioning
confidence: 99%
“…48,49 Designed in accordance with GmP guidelines, the sPrat is used in a number of settings to assess workplacebased performance. although the feasi bility and validity of multisource feedback and patient rating instruments has been reported in various studies, these tools have only been tested on careergrade practi tioners and not specialists; 26,49 no multisource feedback tool has yet been approved for use in specialist recertifica tion. in addition, despite testing in large studies, the reliability and validity of multisource feedback tools in assessing communication and teamwork skills remains to be adequately confirmed.…”
Section: Outcome-based Assessmentmentioning
confidence: 99%